Influence of Propylene Glycol Concentrations in Mangostin Pericarp Extract Gels Formulation: Gels Physical Characteristics, Antibacterial Activity Against Staphylococcus aureus, and Functional Antioxidant Activity Based on Radical 2,2-diphenyl-1-picrylhydrazyl Scavenging Activity - Rina Kuswahyuning; Sylvia Utami Tunjung Pratiwi; Joselin Ekaputri; Meiliana Meiliana (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
Mangostin (Garcinia mangostana L.) fruit pericarp (GMP) extract has been shown to have antimicrobial and antioxidant activities. This study aimed to formulate and evaluate gel formulations of GMP extract using sodium carboxymethylcellulose as a gelling agent and propylene glycol (PG) in varying concentrations (i.e. 0-40%). GMP extract was evaluated for total mangostin content and antioxidant activity based on 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method. Physical gel characteristics were also examined. All gels had similar pH and spreadability, however, gel with 40% PG produced significantly lower viscosity. Antibacterial activities against S.aureus were shown to be the same among GMP extract gels. The antioxidant activity of all GMP extract gels could be confirmed based on the radical DPPH scavenging method. PG content of 40% significantly reduced the increase of GMP extract gel viscosity after being stored for four weeks at room temperature. Additionally, the lowest syneresis was also shown for GMP extract gel with 40% PG content.